2014
DOI: 10.1097/qai.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Mortality in HIV

Abstract: Objective To delineate the association between baseline socioeconomic status (SES) indicators and mortality and lost to follow-up (LTFU) in a cohort of HIV-infected individuals enrolled in antiretroviral treatment (ART) in urban Uganda. Design Retrospective cohort study nested in an antiretroviral clinic-based cohort. Methods SES indicators including education, employment status, and a standardized wealth index, and other demographic and clinical variables were assessed at baseline among ART-treated patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
12
1
1
Order By: Relevance
“…Unemployed urban participants had a higher risk of mortality, a finding that concurs with previous research ( 38 41 ). HIV care was provided at no cost in both sites irrespective of their employment status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unemployed urban participants had a higher risk of mortality, a finding that concurs with previous research ( 38 41 ). HIV care was provided at no cost in both sites irrespective of their employment status.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have shown that mortality could be affected by poor social situations such as unemployment, poor housing, and social isolation. Furthermore, these factors may influence one’s health negatively ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, lower education has also been associated with virologic failure in this cohort (Cardoso et al, 2014), which likely contributes to our findings. Lower education may be an indicator of lower socio-economic status (Szwarcwald, Souza-Junior, & Damacena, 2010), which has also been associated with increased mortality risk (Burkey et al, 2014). We also observed an approximately two-fold increased mortality risk among persons with AIDS defining illnesses, consistent with prior results from our cohort that showed that AIDS defining illnesses increased risk of AIDS-related and non-AIDS related deaths (Grinsztejn et al, 2013) [REF].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, H . pylori infection is considered a disease of poverty, and poor socioeconomic status has been associated with rather disadvantageous outcomes of HIV infection [ 3 ]. The underlying mechanisms for this observed association are unclear.…”
Section: Introductionmentioning
confidence: 99%